2021
DOI: 10.1111/jth.15315
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic factors, inflammatory markers, and risk of incident venous thromboembolism: The Multi‐Ethnic Study of Atherosclerosis

Abstract: Background Several hemostatic factors and inflammatory markers are associated with the risk of incident venous thromboembolism (VTE), however, most existing data are from case‐control studies in Caucasian populations. Objectives We aimed to prospectively confirm previous findings and explore less studied biomarkers in relation to VTE risk in a multi‐racial/multi‐ethnic cohort. Methods Circulating levels of factor VIII, fibrinogen, D‐dimer, plasmin‐antiplasmin complex (PAP), C‐reactive protein (CRP), and interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
(74 reference statements)
6
14
0
Order By: Relevance
“…Among several tested biomarkers, higher D-dimer levels were associated with increased risk of VTE in multivariable-adjusted models [15]. Our results are in line with the previous studies [13][14][15][16]35], as we found that higher D-dimer levels were associated with an increased risk of incident VTE, but according to our results, such an association was partly explained by BMI and inflammation. In fact, none of the aforementioned studies [13][14][15][16]35] made adjustment for low-grade systemic inflammation, as assessed by CRP levels.…”
Section: Atherosclerosis Risk In Communities (Aric) Study and The Car...supporting
confidence: 92%
See 3 more Smart Citations
“…Among several tested biomarkers, higher D-dimer levels were associated with increased risk of VTE in multivariable-adjusted models [15]. Our results are in line with the previous studies [13][14][15][16]35], as we found that higher D-dimer levels were associated with an increased risk of incident VTE, but according to our results, such an association was partly explained by BMI and inflammation. In fact, none of the aforementioned studies [13][14][15][16]35] made adjustment for low-grade systemic inflammation, as assessed by CRP levels.…”
Section: Atherosclerosis Risk In Communities (Aric) Study and The Car...supporting
confidence: 92%
“…The authors later expanded plasma D-dimer measurements in the ARIC population and found that D-dimer levels were related to increased risk of future VTE in a dose-response manner even with more than 10 years of follow-up, in analyses adjusted for age, race, and sex [14]. Additionally, results from the Multi-Ethnic Study of Atherosclerosis (MESA), a prospective cohort with a median of 14 years of follow-up, showed that elevated D-dimer levels were associated with increased risk of incident VTE independently of age, sex, race/ethnicity, education, field center, BMI, diabetes, and estimated glomerular filtration rate [16]. In a nested case-control study (215 VTE cases and 867 controls) derived from the Women's Health Initiative hormone trials, which comprised postmenopausal women, Cushman et al investigated several biomarkers with regards to risk of future VTE [35].…”
Section: Atherosclerosis Risk In Communities (Aric) Study and The Car...mentioning
confidence: 99%
See 2 more Smart Citations
“…21 Second, in vitro studies have shown that activated MASP-2 can cleave prothrombin to thrombin with subsequent fibrin formation, 20,22,23 and several observational studies have shown that a high degree of coagulation activation is associated with the risk of future VTE. [51][52][53][54] Third, experimental studies in mouse models of arterial thrombosis have shown that inhibition of MASP-2, either by genetic deficiency or antibody neutralization, caused smaller myocardial infarct sizes 30,31 and less cerebral infarct volumes and neurological deficits. 28 Supporting these observations, the multiple interactions between the lectin complement pathway and the coagulation system, as well as key complement factors (eg, C3, C5, and the terminal complement complex) that have been shown to associate with the risk of future VTE, are summarized in Figure 6 and Table S4.…”
Section: Discussionmentioning
confidence: 99%